Geogebra como herramienta metodológica para la enseñanza de geometría en el noveno año de EGB paralelo “A” en la unidad educativa Guaranda, periodo 2023-2024. - Chimbolema Agualongo, Mario Rimael (2024)
The research project was developed with the purpose of implementing the application of GeoGebra as a methodological tool in the teaching of geometry in the students of ninth year parallel "A" in the Guaranda Educational Unit period 2023-2024, since they fail to understand the teaching methods that are taught by their teachers, whose consequences are expressed in poor academic performance, therefore, most students are limited due to lack of understanding in the area of exact sciences, especially in the subject of geometry. The methodology has a mixed qualitative- quantitative, descriptive and bibliographic approach with a longitudinal and non- experimental research design, whose methods were deductive and inductive, where two questionnaires with Likert-type answers focused on the students were used, in addition to a semi-structured interview directed to the teacher, choosing a total sample of 35 students and one teacher, being analyzed and processed all the information through statistical computer programs such as Excel and the mathematical software GeoGebra. The results of the research showed the difficulties that students have in learning geometry-related topics, which made it necessary to develop a didactic guide through the GeoGebra program as a methodological tool in the teaching of geometry, concluding that the implementation of this program allows improving learning problems, since it aroused the interest and encouraged the development of critical thinking skills and the resolution of geometric exercises.